Exploring the moderating role of therapist approaches in short-term therapy outcomes for Asian international students - Dou, Diyue; Wang, Han; Xu, Yuanruo (Journal of International Students, 2026)
This secondary data analysis of Xu and Wang (2025) examined whether a therapeutic approach moderated the effects of a pretherapy psychoeducation program on short-term psychotherapy outcomes among Asian international college students. Forty-four participants were randomly assigned to either a psychoeducation-plus-therapy group or a therapy-alone group. The psychoeducation program aimed to enhance mental health literacy, reduce stigma, and increase readiness for therapy. All participants received eight-week individual therapy sessions delivered by doctoral trainees using one of three approaches: psychodynamic, SFBT + CBT, or an integrated approach. Outcomes were assessed using the DASS-21, AIS, ATSPPH, MAKS, and a self-rated distress scale. Multilevel modeling showed that the therapeutic approach moderated changes in DASS-21 scores, with SFBT + CBT and integrated approaches associated with greater reductions in psychological distress and stress than psychodynamic therapy. No significant moderating effects were found for attitudes.